Meaning Of Life For Mothers With Sexually-Abused Children - Sulastri, Sulastri; Khairani, Khairani; Salsabila, Mustamira Sofa (Universitas Islam Negeri Raden Intan Lampung, 2023)
The meaning of life is defined as things that are perceived as necessary, felt useful, and believed to be wonderful and can be used as a life goal. The meaning of life can be discovered in joyful and tragic situations. This research aims to examine the meaning of life among mothers with children who have been sexually abused. This study employs a qualitative method with a case study approach. The research subject is a mother with two sexually abused children. Interviews, observation, and documentation were employed as data-gathering methods. The findings revealed that women who had children who were victims of sexual abuse felt embarrassed, depressed, sad, and exhausted at first. However, the subject always strives to accept what happened to her two children, seeking help from institutes specializing in children. As a result, the subject can still perform positive things like working and expressing support, attention, love, and affection for her children. The subject's meaning of life for the circumstances that occurred to her children caused the subject to grow more attached to them because she was always connected with affection, could live his life with the conditions that transpired, and finally made the subject happy with her children.Keywords: Meaning of life; children as sexual abuse victims; mothers’ meaning of life.